Chemical disinfectants and antiseptics. Quantitative surface test for the evaluation of bactericidal activity of chemical disinfectants and antiseptics used in veterinary area on porous surfaces without mechanical action. Test method and requirements (phase 2, step 2). (25th October 2019) - British Standards Institution,
No abstract available